Thermokinetic behavior of the Al2O3-PbO-B2O3 glasses - Chromcikova, Maria; Svoboda, Roman; Hruska, Branislav; Osipov, Armenak A; Osipova, Leyla M; Pecusova, Beata; Nowicka, Aleksandra; Liska, Marek (Elsevier Science BV, 2022)
Thermokinetic behavior of the Al2O3-PbO-B2O3 glassy system was investigated by means of differential scanning calorimetry, X-ray diffraction analysis and Raman spectroscopy. The glass transition kinetics was described in terms of the Tool-Narayanaswamy-Moynihan model. The compositional evolution of the relaxation parameters was explained in terms of the structural changes and movements of the characteristic structural units detected by Raman spectroscopy. Crystal formation in the studied glassy matrices was investigated in dependence on composition and particle size. The crystal growth was suppressed by increasing particle size as well as by increasing Al2O3 content; formation of crystalline boron oxides was replaced by formation of mixed Al2O3/PbO oxides and Pb4B2O7 phase. The nucleation-growth Johnson-Mehl-Avrami model and the empirical autocatalytic model of.Sestak and Berggren were used to describe the complex crystallization kinetics. The Avramov-.Sestak concept of temperature dependent activation energy was successfully applied and tested on the real-life experimental data. The corresponding methodology was critically reviewed.
Termokinetické chování Al2O3-PBO-B2O3 skel
Keywords: structural relaxation; crystallization kinetics; Avramov-Sestak concept; Al2O3-PbO-B2O3 glasses; strukturní relaxace; krystalizační kinetika; Avramov-Sestak koncept; Al2O3-PBO-B2O3 skla